Bullying and Cyberbullying among LGBQ and Heterosexual Youth from an Intersectional Perspective: Findings from the 2017 National Youth Risk Behavior Survey. (3rd July 2021) - Angoff, Harrison D.; Barnhart, Wesley R.
ABSTRACT: While LGBTQ youth may be victims of bullying at greater rates than heterosexual youth, research examining in-school bullying and cyberbullying victimization disparities through an intersectional framework is limited. Using the 2017 Youth Risk Behavior Survey, the present study examined the prevalence of in-school bullying and cyberbullying victimization across sexual orientation, gender, race, and grade ( N = 13, 567). Results position sexual minority youth at higher odds of experiencing in-school bullying and cyberbullying than heterosexual youth and show that bisexual youth were more likely than gay/lesbian youth to be cyberbullied. Findings from intersectional analyses show within-group variation in bullying victimization across sexual orientation based on gender, grade, and race. Specific intersectional results and implications for in-school bullying and cyberbullying prevention and intervention efforts are discussed.